An application of the Integrated Stake-Tyler Model to an Evaluation of a Task-Based English Course at King Mongkut's Univeesity of Technology Thonburi - Pamararat Wiriyakarun (Chulalongkorn University, 2014)
Thesis (Ph.D.)--Chulalongkorn University, 2007